2017
DOI: 10.3390/molecules22091469
|View full text |Cite
|
Sign up to set email alerts
|

Fructus Ligustri Lucidi in Osteoporosis: A Review of its Pharmacology, Phytochemistry, Pharmacokinetics and Safety

Abstract: Background: Fructus Ligustri Lucidi (FLL) has now attracted increasing attention as an alternative medicine in the prevention and treatment of osteoporosis. This study aimed to provide a general review of traditional interpretation of the actions of FLL in osteoporosis, main phytochemical constituents, pharmacokinetics, pharmacology in bone improving effect, and safety. Materials and Methods: Several databases, including PubMed, China National Knowledge Infrastructure, National Science and Technology Library, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 88 publications
1
45
0
Order By: Relevance
“…Bone and joint diseases, such as osteoarthritis and osteoporosis, are defined as “bone atrophy,” “bone loss,” or “bone rheumatism” in TCM, being attributed to the TCM syndrome of kidney-deficiency ( Guo et al, 2015 ). Meanwhile, FLL exerts bone-protective effect due to its kidney-tonifying activity against kidney deficiency, and has thereby been clinically used to treat osteoporosis and bone metabolic disorders ( Chen et al, 2017 ). Previous studies showed that FLL extract modulated the turnover of bone and the calcium balance in ovariectomized (OVX) rats ( Zhang et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone and joint diseases, such as osteoarthritis and osteoporosis, are defined as “bone atrophy,” “bone loss,” or “bone rheumatism” in TCM, being attributed to the TCM syndrome of kidney-deficiency ( Guo et al, 2015 ). Meanwhile, FLL exerts bone-protective effect due to its kidney-tonifying activity against kidney deficiency, and has thereby been clinically used to treat osteoporosis and bone metabolic disorders ( Chen et al, 2017 ). Previous studies showed that FLL extract modulated the turnover of bone and the calcium balance in ovariectomized (OVX) rats ( Zhang et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was originally recorded in the earliest existing Pharmacopeia “ Shennong Ben Cao Jing” ( Shennong’s Herbal ) during the East Han Dynasty of China (25-220 AD). It has been clinically used for over 1000 years, mainly to treat age-related diseases such as osteoporosis, arthritis, and bone pain ( Pang et al, 2015 ; Chen et al, 2017 ). In the Chinese Pharmacopeia, FLL is recognized as an edible herb with kidney-tonifying activity and is effective in treating soreness and weakness of waist and knees ( China Pharmacopeia Committee, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These methods are less time‐consuming and have satisfactory selectivity. Ligustri Lucidi Fructus (LLF), the fruit of Ligustrum lucidum Ait., is a herbal medicine commonly used in clinical practice in China for nearly two thousand years (Chen et al, ). According to the Chinese Pharmacopoeia (2015 edition), the main function of LLF is to nourish the liver and kidney, brighten eyes, and make hair black (Chinese Pharmacopoeia Committee, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the theory of traditional Chinese medicine, FLL belongs to the hepatic and nephritic meridian that has the effects of cultivating the spirit and nourishing the liver and kidney and it exhibits extensive bioactivities (Pang et al, ). A phytochemistry study suggested that iridoid glycosides were the main bioactive components (Chen et al, ). Among these, the content of specnuezhenide (SPN) was relatively high (Shi, Ma, & Cai, ).…”
Section: Introductionmentioning
confidence: 99%